The Role of Customary Institutions in the Enforcement of Islamic Law in Padang Lawas - Ritonga, Hasir Budiman; Hardana, Ali (Sharia Journal and Education Center Publishing, 2025)
The enforcement of Islamic law in Padang Lawas has its own characteristics because it is influenced by the existence of customary institutions that are still strong in people's lives. The background of this research problem departs from the phenomenon of customary practices that often coexist with Islamic law, but its role in resolving various social disputes has not been fully documented and understood. This research aims to analyze the role of customary institutions in the enforcement of Islamic law, understand customary-based and sharia-based case resolution mechanisms, and see the extent of the effectiveness of customary institutions in maintaining social order in Padang Lawas. The research method used is qualitative with a descriptive approach, through in-depth interviews with traditional leaders, scholars, and communities, as well as documentation studies on customary texts and customary deliberative decisions. The results of the study show that customary institutions play a role as the main mediator in resolving disputes between family, inheritance, and violations of social norms by prioritizing deliberation and the principle of restorative justice. In addition, customary institutions are able to harmonize Islamic and customary values so that law enforcement is created that is accepted by the community. This role is considered effective because it is deeply rooted in local culture and has high moral authority.